2003
DOI: 10.2105/ajph.93.5.759
|View full text |Cite
|
Sign up to set email alerts
|

Male Prisoners and HIV Prevention: A Call for Action Ignored

Abstract: US prison inmates are disproportionately indigent young men of color. These individuals are severely affected by HIV/AIDS, largely owing to the high-risk behavior that they engage in prior to incarceration. Researchers and practitioners have issued a call for the importance of offering HIV prevention services in prison settings. However, this call has largely been ignored. In this article, we outline reasons why these recommendations have been largely ignored, discuss innovative HIV prevention programs that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 11 publications
2
88
0
Order By: Relevance
“…These findings reinforce the notion that men involved in the criminal justice system remain a critical audience for tailored HIV/STI prevention interventions. 42,47,48 This study's findings underscore the importance of HIV/STI prevention research among individuals with low-intensity criminal justice involvement. While there is limited HIV prevention research being conducted in prison settings, 4,49 HIV/STI prevention models targeting short-term jail inmates are virtually nonexistent.…”
Section: Discussionmentioning
confidence: 73%
“…These findings reinforce the notion that men involved in the criminal justice system remain a critical audience for tailored HIV/STI prevention interventions. 42,47,48 This study's findings underscore the importance of HIV/STI prevention research among individuals with low-intensity criminal justice involvement. While there is limited HIV prevention research being conducted in prison settings, 4,49 HIV/STI prevention models targeting short-term jail inmates are virtually nonexistent.…”
Section: Discussionmentioning
confidence: 73%
“…45 However, it is recognized that more needs to be done. 46,47 HIV testing for entrants into correctional settings was universal in some settings, targeted to risk groups in other settings, and offered as voluntary in others. 6 Although the American Medical Association has recommended mandatory HIV 48 Early studies in Oregon and Wisconsin prisons, states with low HIV prevalence, showed high levels of acceptance by inmates of voluntary HIV testing in prison and a high level of detection of HIV infected inmates.…”
Section: Entry and During Incarceration: Prevention Of Infection Tranmentioning
confidence: 99%
“…It would take bold political actions and progressive to impro-ve the health and welfare of the prison population. Among these actions: mandatory adoption of HIV testing in the prison systems, initiatives enhancing continuity of care to the infected inmates returning to the community, better opportunities for community-based organizations and health services to the population incarcerated can have access to education and prevention services to HIV/AIDS [17,32].…”
Section: Thematic Axis 3 Facing Hiv/aids Interventionsmentioning
confidence: 99%
“…However, it is understood that even in prison, the HIV-infected person is a citizen who has rights to health endorsed constitutionally and that the judicial area of rehabilitation is a key opportunity for mass strategies implementations as condom distribution, counseling reduction of risk behaviors, prevention and monitoring of antiretroviral therapy (ARt) [3,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%